Arabic at the Landmark of al-Irsyad Educational Institution (Competence, Cultural Identity & Religious Attitude) - Mustolikh Khabibul `Umam (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2021)
The paper focused on the educational institution of al-Irsyad Tengaran which emphasizes the learning process in Arabic. It is among Arabic competence, social identity and religious attitudes become the reason why Pesantren educational institutions are still existing and developing in some parts of Indonesia. As Islamic pesantren they also prioritize teachings based on purification of Islam free from heresy, superstition and khurafat. This research is a qualitative research method, that can be expected to produce descriptive data in the form of written or spoken words from a number of people and observable behavior. While the approach used is a communicative approach that is an approach with the aim of making communicative competencies as the goal of language learning. In the process of data analysis, there are three main components that must be understood and understood by each researcher. The three components are data reduction, data presentation, and inference or verification. The first step is to standardize arabic competencies that are needed as an evaluation material for their teachers to see how far the students have mastered the Arabic language material that has been taught. it will continue with the development of their way of thinking in the community through the implementation of da'wah training spread in the community as a place to prove their identity as santri al-Irsyad who uphold their educational institutions. The cultural identity that is built will shape their religious attitudes in the society since has been the beginning of Islam echo that is free from religious rituals containing heresy, superstition and khurafat. From these components will form a reason why Arabic is particularly important in the progress and development of educational institutions that have the slogan of restoring the glory of Islam through Arabic.